Requisitos de admissibilidade recursal no novo Código de Processo Civil - Carvalho, Rodrigo Voltarelli de (2016)
To any person (natural or legal) exercise their right of action, which is guaranteed by the 1998 s Constitution of the Federative Republic of Brazil, it is essential that the person fulfill several requirements (conditions of action and procedural assumptions of existence and validity). Failing to do so, that person s conflict will not even be examined by the Judiciary. The same logical reasoning applies to the one who aims to appeal a certain decision: the one who feels aggrieved by any given decision has to fulfill another series of requirements to have its appeal accepted, processed and judge by the Court. This paper studies those requirements that one of the litigants needs to fulfill in order to have its appeal accepted, processed and judge, notoriously known as appeal s admissibility requirements. Centrally, the issues discussed in this paper are those concerning (i) the analysis of the appeal s admissibility requirements expressly set forth in the New Brazilian Civil Procedure Code, (ii) the proper way to fulfill these admissibility requirements, and (iii) the consequences of not fulfilling them when filing an appeal. Therefore, it is necessary the greening of the New Brazilian Civil Procedure Code in the present scenario of Procedure Law in Brazil and identification of those admissibility requirements. Once identified, it will be answered the question about the effects of absence of one of those admissibility requirements, systematizing them in this regard. In early conclusion, it will be noted that the timely filing of an appeal is at the top of the hierarchy of admissibility requirements since it is incurable and since the absence of almost any other of these requirements can be amended